(untitled) (The Journal of Plant Protection Sciences, 2021)
Frenchbean (Phaseolus vulgaris L.) is an 2009. Variety ’Lakshmi’ was sown during important leguminous vegetable grown middle of March in a spacing of 45 X 10 cm in extensively in the hilly region of Darjeeling, the field plot of 200 square meter. West Bengal. In this region, the crop is sown in Recommended agronomic practices were the month of March and harvested in June to followed to raise the crop except the use of any escape low temperature as well as hot or rainy plant protection chemicals. Observations on weather. With the introduction of high yielding pest populations were recorded at weekly varieties and intensive cultivation practices, the interval from fifty plants at random selecting pest problem in this crop might undergo five locations in the field one each in each spectacular changes. Several workers have quarter and one in the middle of ten plants each studied the pest complex of frenchbean in starting one week after sowing till maturity of various parts of the country (1, 2, 3). the crop. The number of jassid and whitefly was Information on the occurrence of pest complex counted visually by observing the lower surface is an essential pre-requisite for developing a of the leaf (trifoliate) after selecting three leaves suitable pest management strategy. However, from upper, middle and lower crop canopy. such information in the context of changing pest Number of leaf folder larvae, leaf beetles and scenario is meagre particularly from this region. Epilachna beetles were counted from each Hence the present investigation was carried out plant. Simple correlations were worked out to generate information on the diversity and between various pests after calculating their abundance of insect pests infesting frenchbean.